2012
DOI: 10.1371/journal.pone.0042028
|View full text |Cite
|
Sign up to set email alerts
|

The Mph1 Helicase Can Promote Telomere Uncapping and Premature Senescence in Budding Yeast

Abstract: Double strand breaks (DSBs) can be repaired via either Non-Homologous End Joining (NHEJ) or Homology directed Repair (HR). Telomeres, which resemble DSBs, are refractory to repair events in order to prevent chromosome end fusions and genomic instability. In some rare instances telomeres engage in Break-Induced Replication (BIR), a type of HR, in order to maintain telomere length in the absence of the enzyme telomerase. Here we have investigated how the yeast helicase, Mph1, affects DNA repair at both DSBs and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

13
32
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(45 citation statements)
references
References 40 publications
(60 reference statements)
13
32
0
Order By: Relevance
“…Consistent with the previous reports (Jain et al 2009;Lydeard et al 2010a;Luke-Glaser and Luke 2012;Stafa et al 2014), single deletion of either Sgs1 or Mph1 increased the efficiency of BIR by twofold ( Figure 3A). In addition, we found that the simultaneous deletion of both Sgs1 and Mph1 increased the efficiency of BIR by nearly fourfold ( Figure 3A).…”
Section: Resultssupporting
confidence: 93%
“…Consistent with the previous reports (Jain et al 2009;Lydeard et al 2010a;Luke-Glaser and Luke 2012;Stafa et al 2014), single deletion of either Sgs1 or Mph1 increased the efficiency of BIR by twofold ( Figure 3A). In addition, we found that the simultaneous deletion of both Sgs1 and Mph1 increased the efficiency of BIR by nearly fourfold ( Figure 3A).…”
Section: Resultssupporting
confidence: 93%
“…Furthermore, Andreassen and colleagues showed that depletion of FANCA or FANCD2 increases the frequency of telomere-free chromosome ends and decreases the tSCE, suggesting that the recruitment of monoubiquitinated FANCD2 to the ALT telomeres promotes HR. Although there is no report that human FANCM is involved in TMM, intriguingly its budding yeast homolog, Mph1, does localize to yeast telomeres and promotes telomere uncapping and premature senescence in the absence of telomerase (55,56).…”
Section: Significancementioning
confidence: 99%
“…MPH1 suppresses BIR during double-strand break repair (Luke-Glaser and Luke 2012;Stafa et al 2014). Given the physical and genetic interactions between Mte1 and Mph1 that our work has revealed, we tested whether MTE1 also plays a role in suppressing BIR.…”
Section: Mte1 Suppresses Birmentioning
confidence: 99%
“…Crossovers can also be prevented if the D-loop structure that results from the first strand invasion by one end of a resected DSB into the homologous chromosome is unwound before capture of the second end to form the dHJ. Unwinding of D-loops is catalyzed in vitro and in vivo by the 39-to-59 DNA helicase Mph1 (Sun et al 2008;Prakash et al 2009) to prevent loss of heterozygosity due to crossovers and break-induced replication (BIR) (Luke-Glaser and Luke 2012;Mazon and Symington 2013;Stafa et al 2014).The Mph1 DNA helicase was first identified as a deletion mutant with an increased mutation frequency (Entian et al 1999). Subsequent characterization revealed that mph1 mutants are sensitive to the alkylating agent MMS and to a lesser degree to ionizing radiation (Scheller et al 2000), and that mph1 mutants are proficient for mitotic recombination (Schurer et al 2004 Here we leverage intracellular protein location data to identify the complement of proteins that colocalize with the recombination repair protein Rad52 in nuclear foci during the response to DNA double-strand breaks.…”
mentioning
confidence: 99%
See 1 more Smart Citation